PROVISION OF FACILITIES, SERVICES AND OPPORTUNITIES FOR LEISURE AND RECREATION TO CURB YOUTH RESTIVENESS IN NIGERIA - Adesogan, Adeniyi Adeola; Mohammed, Awwal Abdullahi; Kambu, Mary Gadzama (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of the study was to reduce the rising menace of youthful restiveness in Nigeria and review research method was rightly adopted due to inaccessibility to volatile place and personalities. Today leisure and recreation have become significant in molding the character and prosperity of people, families, groups and society at large. Leisure can be viewed as a free time judiciously used and recreation as individual or group engagement during leisure time which is for personal enrichments, development and for the good of the community. This smokeless industry constitutes a significant power to our national and local economies and may be answerable for a large number of occupations over such differed fields of sport, entertainment arts and crafts, travel and tourism, dance and music, health and fitness among others. To prevent our youth from engaging in social vices, with huge adverse effect on our cooperate existence as a nation, activities like kidnapping, armed robbery, 419 fraudsters , cattle rustling, terrorist acts, prostitution, cultism, delinquency, political thuggery, rape, vandalism, just to mention but few, all these can be curbed by the provision of facilities, services and opportunities for leisure and recreation. Notwithstanding amiability, relaxation and amusement additionally give significant individual advantages as far as meeting physical, enthusiastic needs and philosophical and other essential wellbeing related requirements for members. In an expansive sense the leisure and recreational existence of a country mirrors its essential esteem and character. The findings of the study clearly show that youths desire leisure, recreational facilities and opportunities to help them property channeled all their aw energies into wholesome and socially acceptable ventures. All concern must jointly provide these facilities. However, participating in leisure and recreation alone will not solve the restiveness in Nigeria but in conjunction with other youth oriented programs, youth restiveness will be meaningfully curbed.